GENETIC AND MORPHOLOGICAL DESCRIPTORS TO ACCESS BRAZILIAN OKRA GENOTYPES DIVERSITY - Carvalho, Fábio Janoni (2022)
Information of the variation for important morphological and physiological traits of okra is still limited. Molecular analysis is an important additional tool in germplasm characterization studies. The study aimed to evaluate the performance of the growth and yield of 20 pre-commercial okra accessions to identify molecular markers’ association with morphological traits. Nineteen morphological traits were measured with five qualitative and 14 quantitative descriptors. For analysis of genetic patterns Random Amplified Polymorphic DNA (RAPD) markers were used with nine primers and 24 usable bands. The genetic dissimilarity was evaluated based in morphological and genetic matrices. Also, graphical representation of genetic distances was obtained by UPGMA and Tocher's optimization method. The morphological characterization of the accessions detected polymorphism for all evaluated traits. RAPD markers were efficient in detecting genetic variability among okra accessions. For the primers used in the experiment, only OPE10 did not amplify the DNA strand. The other eight primers produced a total of 35 bands, in which 25 were polymorphic and ten were monomorphic. The morphological traits and molecular markers identified wide genetic variability among the 20 okra accessions, indicating successful crosses in breeding programs and isolating some interesting materials. Morphological and molecular cluster analyses were complementary and helped in the genotype selection. Molecular analysis indicated some divergent accessions that were not found in morphological analysis, which could highlight some materials that have a desirable trait, that is difficult and highly costly to access in field experiments.